2020
DOI: 10.21608/zumj.2020.36662.1902
|View full text |Cite
|
Sign up to set email alerts
|

Values and predictive factors for Success of Methotrexate Therapy in Medical Management of Ectopic Pregnancy

Abstract: Background: Using Methotrexate as an option for medical treatment of ectopic pregnancies has been suggested since 1982. Studies regarding the dose, number of doses of methotrexate and the predictive factors of degree of success of methotrexate in the medical management of ectopic pregnancy are limited. Aim of the present article were; to assess the predictive factors of success and efficacy of methotrexate therapy and to assess the value and efficacy of using lower dose of methotrexate and the suitable number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…In 1980 Tanaka et al introduced methotrexate as a successful treatment option for EP first time. 19 Our study showed the success rate of the methotrexate treatment in EP 73% which is lower as compared to 89%, 90.2% as found in other studies 20,21 .…”
Section: Discussioncontrasting
confidence: 58%
“…In 1980 Tanaka et al introduced methotrexate as a successful treatment option for EP first time. 19 Our study showed the success rate of the methotrexate treatment in EP 73% which is lower as compared to 89%, 90.2% as found in other studies 20,21 .…”
Section: Discussioncontrasting
confidence: 58%